TINGKAT KEPUASAN KONSUMEN KUE â€œROKUPANGâ€ DI KOTA MANADO (Level of Customer Satisfaction of Cake "Rokupang" in Manado City) - Tesalonika Ariela Apouw; Melissa L. G. Tarore; Leonardus R. Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to determine the level of customer satisfaction of the cake "Rokupang" based on the product, price, place, promotion, and service variables. This research was conducted from January to March 2020. The data used in this study were primary data and secondary data. Primary data were taken by survey by direct interviewing 42 respondents using a questionnaire. Respondents were selected using the accidental sampling method. Secondary data were taken from the business management. Measurement of the level of satisfaction was carried out using a Likert scale and followed by an analysis of the consumer satisfaction index. The results showed that the general level of customer satisfaction in Rokupang based on product, price, place, promotion, service variables was 76.47%, which falled into the satisfied category. When looked per variable, it was found that for prices and products were included in the very satisfied category, where prices got a value of 86% and products are 85%. Meanwhile, the variables of Place (74.00%), Service (71.00%), and Promotion (68.81%) falled only into the satisfied category.